Carbamide peroxide gel stability under different temperature conditions: is manipulated formulation an option? - Camila de Martini Bonesi; Letícia Storchi Ulian; Paula Balem; Valeria Weiss Angeli (Universidade de São Paulo, 2011)
Nowadays the use of gel containing carbamide peroxide (CP) prepared in Pharmacy is a normal practice in the population. However, the quality of this product is questionable concerning its stability. The aim of this study is was to synthesize and to analyze this drug alone or associated to Carbopol gel through analytical methodology compatible with the routine of the Pharmacies. The reaction between urea and hydrogen peroxide was carried out at different resting times: 24 hours (CP 24 powder) and 48 hours (CP48 powder) after the mixture. Both products were associated with Carbopol 940® gel 1.5% (G) generating G24 and G48 samples. The stability of powders (CP24 e CP48) and the formulations (G24 and G48) were evaluated as a function of time (15, 40 and 45 days) and thermal variation (refrigeration: 8 °C±1; thermal shock 32 °C±1 /8 °C±1; stove: 32 °C±1), using a standard titration method. As a result, only under refrigeration the CP24 and CP48 contents remained stable during the period of 45 days. An interesting finding was that G24 and G48 presented greater stability for at least 45-days under refrigeration and thermal shock conditions, and up to 30 days under stove conditions. The results for the G24 and G48 were slightly higher than those obtained for the control. Therefore, we were able to conclude that association with Carbopol 940® Gel 1.5 % provided greater CP stability and that manipulated formulations containing CP may be viable for use in a period of 45 days under refrigeration conditions. The titration proved to be an effective technique for the analysis of CP with or without Carbopol 940® gel 1.5%. Atualmente, a utilização de gel contendo peróxido de carbamida manipulado em Farmácia é uma prática comum na população. No entanto, a qualidade deste produto é questionada, sobretudo no que se refere à estabilidade deste fármaco. O objetivo deste trabalho consiste na avaliação da viabilidade de sintetizar e analisar quantitativamente este fármaco associado ou não a um gel de Carbopol através de metodologia analítica compatível com a rotina das Farmácias. A reação entre a uréia e o peróxido de hidrogênio foi realizada em tempos diferentes de repouso após a mistura, 24 h para sintetizar o pó PC 24 e 48 h para o pó CP 48. Estes pós foram associados a um gel (G) de Carbopol 940® 1,5 %, originando as amostras G24 e G48. A estabilidade dos pós (PC 24 e PC 48) e das formulações (G 24 e G 48) foi avaliada em função do tempo (15, 40 e 45 dias) e da variação térmica (refrigeração: 8 °C±1; choque térmico: 32 °C±1/8 °C±1 e estufa: 32 °C±1), através da técnica de titulometria. Os resultados indicam que unicamente sob refrigeração o CP24 e o CP 48 mantiveram-se estáveis no período de 45 dias. O G24 e o G48 apresentaram estáveis por pelo menos 45 dias nas condições de refrigeração e choque térmico e por 30 dias na condição estufa. Os resultados obtidos para o G24 e G48 foram ligeiramente superiores aos obtidos para o controle. Além disso, é possível concluir que a associação do PC com o gel de Carbopol 940® 1,5 % promoveu um aumento na estabilidade do PC e que as preparações manipuladas contendo PC são viáveis para uso durante um período de 45 sob refrigeração. A titulometria mostrou-se uma técnica eficaz para a análise do PC associado ou não ao gel de Carbopol 940® 1,5%.